We start by assuming the parametrized loading, in which the total external load vector is expressed as
where
![$ f$](img113.png)
is proportional, reference load vector, and
is load scaling parameter,
The arc-length method is based on idea of controlling the length passed along the loading path. For the differential length of loading path we can write
![$\displaystyle \Delta l = \sqrt{\Delta\mbox{\boldmath$r$}^T\Delta\mbox{\boldmath$r$}+(c^2\Delta\lambda^2\mbox{\boldmath$f$}^T_p\mbox{\boldmath$f$}_p)}$](img188.png) |
(2.3) |
where
is coefficient of generalized metrics used to define
(taking into account different units of displacement and load).
For selected increment of loading path length
, we are looking for the equilibrium, where the unknowns are nodal displacements
and the load scaling parameter
. We have the equilibrium equation and additional scalar equation 2.3:
Figure 2.2:
Illustration of Acr-length method
|
At the end of n-th loading step and i-th iteration the displacement vector can be written as
![$ r$](img5.png)
![$ r$](img5.png)
![$ ^{i-1}_n+\delta$](img200.png)
and similarly the load scaling parameter as
. Substituting this into equilibrium equation 2.4 we get
By linearization of
![$ F$](img100.png)
around known state
![$ r$](img5.png)
we get
and finally for unknown
![$ \delta$](img95.png)
Note that the vectors
![$ \delta$](img95.png)
![$ r$](img5.png)
and
![$ \delta$](img95.png)
![$ r$](img5.png)
can be computed and the only unknown remaining is the incremental change of loading parameter
, which could be determined from 2.5
This finally yields a quadratic equation for unknown increment of loading parameter
. The algorithm is summarized in Table
.
Table 2.2:
Newton-Raphson method
Given |
|
![$ f$](img113.png) ![$ f$](img113.png) ![$ _p$](img186.png) |
|
![$ r$](img5.png) ![$ r$](img5.png) ![$ _{n-1}$](img168.png) |
|
Evaluate |
|
![$ \;\;\delta$](img218.png) ![$ r$](img5.png) ![$ _\lambda = ($](img219.png) ![$ K$](img7.png) ![$ _n)^{-1}$](img220.png) ![$ f$](img113.png) ![$ _p$](img186.png) |
|
![$ \;\;\Delta\lambda^0=\pm{\Delta l}/{\sqrt{\delta\mbox{\boldmath $r$}_\lambda^T\...
...mbox{\boldmath $r$}_\lambda+c^2\mbox{\boldmath $f$}_p^T\mbox{\boldmath $f$}_p}}$](img221.png) |
|
![$ \;\;\Delta$](img222.png) ![$ r$](img5.png) ![$ _n^0 = ($](img223.png) ![$ K$](img7.png) ![$ _n)^{-1}(\Delta\lambda$](img224.png) ![$ f$](img113.png) ![$ _p) = ($](img225.png) ![$ K$](img7.png) ![$ _n)^{-1}((\lambda_n+\Delta\lambda^0)$](img226.png) ![$ f$](img113.png) ![$ f$](img113.png) ![$ ^{int,0}_n)$](img228.png) |
|
Repeat for
![$ i=1,2,\cdots$](img172.png) |
|
![$ \;\;\delta$](img218.png) ![$ r$](img5.png) ![$ _\lambda = ($](img219.png) ![$ K$](img7.png) ![$ _n^{i-1})^{-1}$](img229.png) ![$ f$](img113.png) ![$ _p$](img186.png) |
|
![$ \;\;\delta$](img218.png) ![$ r$](img5.png) ![$ _r = ($](img230.png) ![$ K$](img7.png) ![$ _n^{i-1})^{-1}(\lambda_n^{i-1}$](img231.png) ![$ f$](img113.png) ![$ _p -$](img227.png) ![$ f$](img113.png) ![$ ^{int}($](img170.png) ![$ r$](img5.png) ![$ _n^{i-1}))$](img232.png) |
|
Solve quadratic equation 2.7 for
![$ \delta\lambda$](img212.png) |
|
![$ \;\;\delta$](img218.png) ![$ r$](img5.png) ![$ ^i = \delta$](img234.png) ![$ r$](img5.png) ![$ _r+\delta\lambda\delta$](img235.png) ![$ r$](img5.png) ![$ _\lambda$](img211.png) |
|
![$ \;\;\Delta$](img222.png) ![$ r$](img5.png) ![$ _n^i = \Delta$](img236.png) ![$ r$](img5.png) ![$ ^{i-1}+\delta$](img237.png) ![$ r$](img5.png) ![$ r$](img5.png) ![$ r$](img5.png) ![$ _n^{i-1}+\delta$](img240.png) ![$ r$](img5.png) ![$ ^i$](img180.png) |
|
![$ \;\;\lambda^i = \lambda^{i-1}+\delta\lambda,\ \Delta\Lambda_n^i = \Delta\Lambda_n^{i-1}+\delta\lambda$](img241.png) |
|
Until convergence reached |
|
|
Borek Patzak
2017-12-30